A hierarchical approach for modeling X‐ray beamlines: application to a coherent beamline. (18th October 2019) - Sanchez del Rio, Manuel; Celestre, Rafael; Glass, Mark; Pirro, Giovanni; Herrera, Juan Reyes; Barrett, Ray; da Silva, Julio Cesar; Cloetens, Peter; Shi, Xianbo; Rebuffi, Luca
Abstract : A hierarchical scheme of the calculations of an X‐ray beamline for coherent applications is presented. Starting from simple calculations to partial coherence calculations, ray‐tracing and wave optics software are applied to simulate the beamline performances. Abstract : Different approaches to simulate a modern X‐ray beamline are considered. Several methodologies with increasing complexity are applied to discuss the relevant parameters that quantify the beamline performance. Parameters such as flux, dimensions and intensity distribution of the focused beam, and coherence properties are obtained from simple analytical calculations to sophisticated computer simulations using ray‐tracing and wave optics techniques. A latest‐generation X‐ray nanofocusing beamline for coherent applications (ID16A at the ESRF) has been chosen to study in detail the issues related to highly demagnifying synchrotron sources and exploiting the beam coherence. The performance of the beamline is studied for two storage rings: the old ESRF‐1 (emittance 4000 pm) and the new ESRF‐EBS (emittance 150 pm). In addition to traditional results in terms of flux and beam sizes, an innovative study on the partial coherence properties based on the propagation of coherent modes is presented. The different algorithms and methodologies are implemented in the software suite OASYS . These are discussed with emphasis placed upon the their benefits and limitations of each.